(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
The article contains tactical information on how remotely controlled robotic device operate in emergency situations, as well as information on monitoring the situation, improving work efficiency by ensuring the safety of rescuers and providing assistance to them in emergency situations, as well as information on research and experiments conducted in this direction in foreign countries. Information is provided on the role of robotic device in emergency situations, the development of a monitoring model and the main technical indicators. The results of research and testing have confirmed that the capabilities of this newly developed robotic device are consistent with the original specifications and tactics.